Energy-Efficient Chain Formation Algorithm for Data Gathering in Wireless Sensor Networks. (10th September 2012) - Lim, Se-Jung; Park, Myong-Soon
Abstract : In wireless sensor networks, since sensor nodes are distributed in inaccessible regions for data gathering, they need to be operated during an assigned time without battery recharging and relocation. For this reason, there has been abundant research on improving energy efficiency. PEGASIS, one of the well-known chain-based routing protocols for improving energy efficiency, builds a chain based on the greedy algorithm. However, due to long communication distance of some sensor nodes in a chain formed by the greedy algorithm, unbalanced energy consumption of sensor nodes occurs. Eventually, the network lifetime from this cause decreases. We propose energy efficient chain formation (EECF) algorithm to resolve the unbalanced energy consumption problem caused by long-distance data transmission of some nodes in a chain formed by the greedy algorithm. The simulation results are used to verify the energy consumption balance of sensor nodes and the whole network lifetime. In simulation, it is shown that EECF produces better results than the greedy algorithm.